Programação integrada aplicada à automação de projetos: uma aplicação em exaustores para aviários - Liesenfeld, Alexssander Ariel Kuhn (2017)
This paper deals with an alternative in the execution of an exhaust-fan project used in aviary, fully automatized. In order to achieve that intention, the integration of a 3D CAD software (SolidWorks®) through its API and another software responsible for allowing the coding of macros is used (Visual Basic for Applications®), and when in performance, it creates the entire purpose of the equipment. User interaction interfaces are used to determine the equipment’s main geometric measurements and this data is sent to the macro, converting them so that they are compatible with what is required for the execution and the start of the exhaust-fan modeling. At the end of the coding execution, the user will have the complete design of an exhaust-fan according to the defined measures. The design of the equipment will be saved in the directory entered by the user, in 3D CAD software format, as well as in PDF file format for detailing. This way, files can be opened even on computers/machines that do not have a 3D CAD software. Considering the importance of the work for designers and lay students in programming, a book was published so that one can verify all the aspects presented in this paper and, besides being able to develop this same project, also making any other kind of automation within the software. The electronic address for accessing this material is: "https://goo.gl/9lKCuN".